2016
DOI: 10.1542/peds.2016-0491
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Victims of Snakebites: 2000–2013

Abstract: The epidemiology of pediatric snakebites is changing. One-half of the reported exposures were venomous, and copperhead bites and exotic species are being reported more frequently. Although snakebite-related deaths are rare, ICU admission is common. Antivenom treatment is incompletely reported, but its use is increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
4
25
2
Order By: Relevance
“…An analysis of 20 years of National Vital Statistics System data found three southern states—Texas, Florida, and Georgia—accounted for 44% of venomous snakebite deaths in the USA 2 40. In a pediatric snakebite registry review, most cases were reported in Texas, Florida, Georgia, North Carolina, Arizona, and California 41. Concordantly, our data indicate that 82% of snakebites occurred in the South, 11% in the West, 7% in the Midwest, and 1% in the Northeast.…”
Section: Discussionsupporting
confidence: 67%
“…An analysis of 20 years of National Vital Statistics System data found three southern states—Texas, Florida, and Georgia—accounted for 44% of venomous snakebite deaths in the USA 2 40. In a pediatric snakebite registry review, most cases were reported in Texas, Florida, Georgia, North Carolina, Arizona, and California 41. Concordantly, our data indicate that 82% of snakebites occurred in the South, 11% in the West, 7% in the Midwest, and 1% in the Northeast.…”
Section: Discussionsupporting
confidence: 67%
“…This correlates with various studies with higher incidence in males. This is consistent with various adult as well as pediatric studies with69% males in study by Sankar et al, 68% males by Schulte et al, 60.55% males and male to female ratio of 1.5:1 by Halesha B.R et al [7][8][9] . Lower extremity is the most commonly bitten site and is comparable to other studies around 70 to 80% 6,9-12 .…”
Section: Discussionsupporting
confidence: 89%
“…Only Texas, Florida, and Georgia experienced higher call rates during this period. 21 However, PCC calls may represent an underestimation of the total number of statewide snakebites. A comparison of snakebite-related Missouri PCC calls and ED visit data found that only 18% of snakebite-related ED visits had a corresponding call to the state poison center.…”
Section: Discussionmentioning
confidence: 99%